Strategi Kepemimpinan Kepala Madrasah dalam Meningkatkan Kemandirian Siswa di MTS Awirrasyidin di Medan - Putri Handayani; Sakban Lubis; Charles Rangkuti (Medan Resource Center, 2026)
This study aims to describe the leadership strategies employed by madrasah principals in enhancing student independence at MTs Awirasyidin Medan. The research adopts a qualitative approach using a case study method. Data were collected through interviews, observations, and documentation involving the principal, teachers, and students. Data analysis was conducted interactively through the processes of data reduction, data display, and conclusion drawing. The findings indicate that the madrasah principal plays a crucial role in developing a religious and character-based school culture through exemplary leadership, guidance, and instructional innovation. The strategies implemented include strengthening leadership practices, developing a character-based curriculum, increasing student participation in school activities, and implementing a reward and mentoring system that fosters responsibility and motivation. Furthermore, the madrasah principal integrates the values of independence into classroom learning, extracurricular programs, and the broader madrasah culture. Several challenges were identified, including limited resources and varying levels of student motivation. However, these challenges were addressed through collaboration, the optimization of teachers’ potential, and the application of a spiritual approach. Overall, the madrasah principal’s inspirational and participatory leadership, grounded in Islamic values, has proven effective in enhancing students’ discipline, responsibility, and independence.